An evaluation of the level of awareness of Broadband over Power Lines (BPL) and its standard / Norlizawati Nawi - Nawi, Norlizawati (2006)
This study discusses a new technology called Broadband over Power Lines (BPL) technology that utilizes the electricity power lines for the internet use or broadband. The discussion is on the awareness of Malaysians about the technology and its standard. Since this is a new technology in Malaysia, a few approaches is applied in order to acquire data and technical information by interviewing personnel that have relation with the technology, gathering information from the Internet, IEEE Journals, books, magazines and keep track with the latest news on power line technology through newspaper. From the research, we acknowledged that the level of awareness of broadband over power lines is still low but the expectations and the acceptance of BPL are very high. The result also shown that BPL is more effective and the performance is beyond our first impression when we aware about BPL than the formal broadband. The main constraint In conducting this research is difficulties in obtaining the real data and technical information since the technology is not yet been implemented in Malaysia. But once the technology is being implemented in Malaysia, hopefully by the next year, our Information Society that hunger for a high speed Internet connection will enjoy the features offered by the technology.